STATISTICAL ANALYSIS OF PUBLIC ADMINISTRATION PAY - Elena I. Dobrolyubova (Статистика и экономика)
This article reviews the progress achieved inimproving the pay system in public administration and outlines the key issues to be resolved.The cross-country comparisons presented inthe article suggest high differentiation in pay levels depending on position held. In fact,this differentiation in Russia exceeds one in OECD almost twofold The analysis of theinternal pay structure demonstrates that thelow share of the base pay leads to perversenature of ‘stimulation elements’ of the paysystem which in fact appear to be used mostlyfor compensation purposes. The analysis of regional statistical data demonstrates thatdespite high differentiation among regionsin terms of their revenue potential, averagepublic ofﬁcial pay is strongly correlated withthe average regional pay.